Quantitative Measurement of the Thyroid Uptake Function of Mouse by Cerenkov Luminescence Imaging - Chien-Chih Ke (Nature Portfolio, 2017)
Abstract Cerenkov luminescence imaging (CLI) has been an evolutional and alternative approach of nuclear imaging in basic research. This study aimed to measure the 131I thyroid uptake of mouse using CLI for assessment of thyroid function. Quantification of 131I thyroid uptake of mice in euthyroid, hypothyroid and hyperthyroid status was performed by CLI and γ-scintigraphy at 24 hours after injection of 131I. The 131I thyroid uptake was calculated using the equation: (thyroid counts − background counts)/(counts of injected dose of 131I) × 100%. Serum T4 concentration was determined to evaluate the thyroid function. The radioactivity of 131I was linearly correlated with the CL signals in both in vitro and in vivo measurements. CLI showed a significant decrease and increase of 131I thyroid uptake in the mice in hypo- and hyperfunctioning status, respectively, and highly correlated with that measured by γ-scintigraphy. However, the percent thyroid uptake measured by CLI were one-fifth of those measured by γ-scintigraphy due to insufficient tissue penetration of CL. These results indicate that CLI, in addition to nuclear imaging, is able to image and evaluate the 131I thyroid uptake function in mice in preclinical and research settings.